Polymorphous Adenocarcinoma: A Rare Case Report with Unique Radiographic Appearance on CBCT - Jagadish Chandra; Junaid Ahmed; K. M. Veena; M. Vijayakumar; Nandita Shenoy; Nanditha Sujir (Case Reports in Dentistry)
Background. Polymorphous low-grade adenocarcinoma (PLGA) is a slow growing malignant tumor of minor salivary glands and is generally of indolent nature. However, according to the most recent WHO Classification of Salivary Gland Tumors (2017), the cancer is classified as Polymorphous AdenoCarcinoma (PAC). PAC presents as a less aggressive tumor, though it could on rare occasions demonstrate distant metastasis. Case Presentation. A 47-year-old man who was referred by a private practitioner for a CBCT scan in reference to a proliferative soft-tissue growth in the hard palate. The growth was mild and tender and there was Grade III mobility in relation to all the maxillary teeth. Panoramic radiograph taken previously had revealed evidence of alveolar bone loss in relation to the maxillary teeth and was inconclusive of any other findings. The CBCT scan revealed evidence of moth-eaten appearance of maxilla with destruction of medial and lateral walls and floor of maxillary sinus. There was also evidence of involvement of right eustachian tube, ethmoidal wall, and nasopalatine canal. An intraosseous malignancy of the palate was suspected, and a total maxillectomy was performed. The tissue sample was sent for histopathological assessment wherein changes diagnostic for polymorphous low-grade adenocarcinoma of the palate were observed. Conclusion. PAC is a distinct, yet commonly occurring, minor salivary gland tumor with varied clinical and histologic appearance. This case report highlights the importance of CBCT in diagnosing the intraosseous involvement of such tumors which can help shed some light in enhancing our knowledge about the minor salivary gland malignancies like PAC.